Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/molecules26020506
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Potential Application of EC-Synthetic Retinoid Analogues in Anticancer Therapy

Abstract: (1) Background and Aim: All-trans retinoic acid (ATRA) induces differentiation and inhibits growth of many cancer cells. However, resistance develops rapidly prompting the urgent need for new synthetic and potent derivatives. EC19 and EC23 are two synthetic retinoids with potent stem cell neuro-differentiation activity. Here, these compounds were screened for their in vitro antiproliferative and cytotoxic activity using an array of different cancer cell lines. (2) Methods: MTT (3-(4,5-dimethylthiazol-2-yl)-2,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 153 publications
(181 reference statements)
4
25
0
Order By: Relevance
“…When we constructed PPI networks of molecules elevated by cDNA microarray and proteomic analysis, both networks were similar ( Supplementary Figures S1 and S2 ). Although there are many reports on the induction of cancer cell differentiation and growth inhibition [ 47 , 48 ], there are almost no reports on the involvement of HBp17. It was reported that FLG expression increases in HBp17 -KO mice [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…When we constructed PPI networks of molecules elevated by cDNA microarray and proteomic analysis, both networks were similar ( Supplementary Figures S1 and S2 ). Although there are many reports on the induction of cancer cell differentiation and growth inhibition [ 47 , 48 ], there are almost no reports on the involvement of HBp17. It was reported that FLG expression increases in HBp17 -KO mice [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The developed color, due to soluble formazan, was read at 570 nm with a microplate reader (800TSUV Biotek ELISA Reader, Agilent, Santa Clara, CA, USA), and corresponding optical densities were used for calculation of IC 50 . The corresponding selectivity index was calculated based on IC 50 values of the pine extract and abietic acid on both noncancerous and cancerous cells according to Equation (1) [ 24 , 91 ]: SI = IC 50 (non-cancerous cells)/IC 50 (cancerous cells) …”
Section: Methodsmentioning
confidence: 99%
“…Abdelaal MR. et al. reported that EC-synthetic retinoids can be effective, alone or in combinations, for a potential anticancer activity to colorectal cancer, with overexpression of E-cadherin, RAI2, and Werner (WRN) genes ( 39 ). Both 5-Aza-2′-deoxycytidine (DAC, a demethylation agent) and retinoic acid could induce the expression of RAI2 in colorectal cancer, which was proved in our previous ( 24 ) and supplementary data of this study.…”
Section: Discussionmentioning
confidence: 99%